The History and the Art of Anatomy: a source of inspiration even nowadays - Mavrodi, Alexandra; Paraskevas, George; Kitsoulis, Panagiotis (Italian Journal of Anatomy and Embryology, 2013)
Ever since man started to study systematically medicine for the first time he recognized the value of the knowledge of Anatomy in order to safely cut and treat the human body. However, over the centuries it has been proved that Anatomy is more than just a scientific field of medicine. The fact that Anatomy requires the use of human cadavers as an object to study brought to the surface many moral issues, which adumbrated its turbulent past. Additionally, Anatomy and its inextricable element, illustration, has many times been a source of inspiration for both the anatomists and the artists. This paper aims on the one hand to provide a condensed overview of the history of Anatomy and on the other hand to investigate the way Anatomy penetrates Art and, conversely, Art penetrates Anatomy.